Entrepreneurial Values On Business Performance: Entrepreneurial Commitment As A Mediation - Titiek AMBARWATI; Ery Tri DJATMIKA; Puji HANDAYANTI (Indonesia Strategic Sustainability, 2022)
The business world today is also starting to develop along with business competition, whether on a small, medium or large scale. One of them is Micro, Small and Medium Enterprises (MSMEs). The purpose of this study was to analyze entrepreneurial values such as self-efficacy and achievement motivation on business performance, and entrepreneurial commitment as mediating variables. This research was conducted in MSMEs in Malang City and involved 100 respondents, namely business owners. This study is quantitative using explanatory research. The explanatory research aimed to test a theory or hypothesis in order to support or reject the theory or hypothesis from previous research results. The data analysis used path analysis with Partial Least Square (PLS) software (SmartPLS 3.0). The objective of this study was to examine the effects between variables (self-efficacy, achievement motivation, entrepreneurial commitment, and business performance). The results of this study are the influence of self-efficacy on entrepreneurship commitment and performance, achievement has a significant effect on business performance, but not significant on entrepreneurial commitment, then entrepreneurship commitment on business performance, and has a mediating role between self-efficacy on business performance. Meanwhile, entrepreneurship commitment does not mediate the effect of motivation on business performance. Further research can be done by adding other variables and seeing whether entrepreneurship commitment can strengthen the influence of motivation on business performance through a moderation test.